2010
DOI: 10.1002/jmv.21825
|View full text |Cite
|
Sign up to set email alerts
|

Virological and immunological features of active cytomegalovirus infection in nonimmunosuppressed patients in a surgical and trauma intensive care unit

Abstract: Cytomegalovirus (CMV) reactivation occurs frequently in critically ill patients. The natural course of CMV infection and the interaction between CMV and the adaptive immune system in this setting remain poorly defined. Fifty‐three CMV‐seropositive patients in a surgical and trauma intensive care unit were included in this study. The CMV DNA load in tracheal aspirates (TA) and plasma (PL) was monitored by qPCR. CMV‐specific T‐cell immunity was assessed by intracellular cytokine staining. Plasma TNF‐α levels wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
51
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 32 publications
(48 reference statements)
12
51
0
2
Order By: Relevance
“…Based on the author's knowledge, this high prevalence of HHV6 among HHVs is not reported by other prospective studies on ventilated pediatric patients at the PICU. Although there was no significant differences between clinical outcome (mortality) in VAP+/HHV+ and VAP+/HHVgroups (P value: 0.326), yet patients with positive HHVs had greater mortality (24.7%), which is in agreement with previous reports (13,21,(41)(42)(43)(44)(45). On the other hand, patients with VAP (+) had a greater chance of HHVs positivity (36.8%) than VAP (-) patients (18.7%) (P value = 0.124) (34).…”
Section: Discussionsupporting
confidence: 92%
“…Based on the author's knowledge, this high prevalence of HHV6 among HHVs is not reported by other prospective studies on ventilated pediatric patients at the PICU. Although there was no significant differences between clinical outcome (mortality) in VAP+/HHV+ and VAP+/HHVgroups (P value: 0.326), yet patients with positive HHVs had greater mortality (24.7%), which is in agreement with previous reports (13,21,(41)(42)(43)(44)(45). On the other hand, patients with VAP (+) had a greater chance of HHVs positivity (36.8%) than VAP (-) patients (18.7%) (P value = 0.124) (34).…”
Section: Discussionsupporting
confidence: 92%
“…However, in another study using different immunological methods, active CMV infection was reported in septic shock patients despite detectable levels of CMV-specific IFN-c-producing CD4? T cell precursors in blood, suggesting that CMV reactivation is not primarily triggered by T cell immunosuppression [22]. CMV-specific T cell immunity (CD4?)…”
Section: Pathophysiology Of CMV Infectionmentioning
confidence: 99%
“…This heterogeneity makes interpretation of the distinct proportions of patients with HCMV presence found in these studies (from 8.3% to 55.2%) difficult. In four studies in which identical approaches for detection of HCMV (real-time PCR) were used for equivalent specimens as in our study, HCMV DNA was demonstrated in 8.3% to 33% of patients in plasma and in 55.2% of patients in blood [5,7,10,12]. Even comparison of these results may be biased by distinct sensitivities (and specificities) of the assays used in individual study.…”
Section: Discussionmentioning
confidence: 67%
“…In the last decade the role of serious infections in activation of latent HCMV infection in immunocompetent patients also is being scrutinised. The studies comprised critically ill patients treated at intensive care units (ICU) [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%